THE INFLUENCE OF THE BOARDING SCHOOL ENVIRONMENT ON STUDENTS' ACADEMIC VALUES AT MA Al-MUBAROK - Uswatun Hasanah; Mohamad Din Hadi (LP2M IAIN Sultan Amai Gorontalo, 2024)
This study aims to examine the influence of the pesantren environment on students’ academic achievement at MA Al-Mubarok. The pesantren environment is viewed as an educational ecosystem that integrates formal and nonformal education through discipline, religious values, literacy culture, and social interaction among students. This research employed a qualitative descriptive approach. The research subjects included students residing in the pesantren, subject teachers, and pesantren administrators, selected through purposive sampling. Data were collected through observation, semi-structured in-depth interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the pesantren environment has a positive impact on students’ academic achievement. Time discipline, religious habituation, literacy practices, Arabic language learning, and collective learning culture contribute to the enhancement of students’ learning motivation, psychological well-being, and academic understanding. This study confirms that the pesantren environment functions not only as a space for character building but also as an effective educational system that supports students’ academic success in madrasah-based education.